A Simplified Strengthening Methodology for Minaret Structures in Turkey: Hagia Sophia Case - Korkmaz, Kasım A. (International Journal of Architectural Engineering Technology, 2017)
Considering various types of historical buildings in Turkey, mosqs are the most common ones. Mosqs have minaret structures standing along next to the main body with dome. The minaret buildings with their own architectural and structural characteristics, are representing the cultural and historical change in different periods over the centruies. Minarets from Ottomon period are the most widespread ones in Turkey. With its cultural synthesis through out the history, minarets from Ottomon period differ from the others with structural capability. Since Turkey is a earthquke prone country, it is very important to make existing historical structures stronger against to the seismic loads. Recently, historical structures have been strengthened with fiber reinforced polymer (FRP) composites. There are numerous of research studies are available related with strengthening using FRP composites. From this standing point, in this research, a simplified and practicale strengthening methodlogy is proposed. For the investigation Hagia Sophia Minaret structures has been used as a case study. In the analysis part, Hagia Sophia Minaret structures have been investigated through time history analyses before and after FRP composite strengthening. As a result of the present research work, displacements and stress values are determined for comparison of the structural behavior of minaret structures.